'I Love Being the Teacher with an Accent': A Counterstory from a Former Refugee from Sudan. (1st May 2019) - Kodi, Iglal; Thapliyal, Nisha
Teachers from culturally and linguistically diverse (CALD) backgrounds are underrepresented in the Australian teaching profession. Furthermore, teachers ostracising in their everyday experiences of teaching and social interaction in Australian schools. This paper presents a counterstory of the educational journey of a Sudanese Australian teacher and former refugee who arrived in Australia as a teenager. Iglal journey towards becoming a teacher began in Sudan, continued in Egypt and came to fruition in Australia. This article documents the spiritual, emotional and mental hard work of the storyteller to overcome barriers to her education. It makes connections between lived experience and larger social contexts that shape experiences of education in resettlement contexts. It is hoped that the findings will inform not only initiatives to diversify the teaching profession, but also efforts to create and sustain globally aware and active teachers regardless of their cultural background.